2019 Computing in Cardiology Conference (CinC) 2019
DOI: 10.22489/cinc.2019.379
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Activation Times Estimation for Potential-Based ECG Imaging

Abstract: Activation times (AT) represent the sequence of cardiac depolarization and are one of the most important parameters of cardiac electrical activity. However, estimation of ATs is challenging due to multiple sources of noise. If ATs are estimated from signals reconstructed using electrocardiographic imaging (ECGI), additional problems can arise due to over-smoothing or ambiguities in the inverse problem. Resulting AT maps can show falsely homogeneous regions or artificial lines of block. As ATs are not only impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…We adopted the mean ± standard deviation of Pearson's correlation coefficient ( Bear et al., 2018 ; Schaufelberger et al., 2019 ; Serinagaoglu Dogrusoz et al., 2019 ) as a measure of disagreement between our inference predictions and the ‘target data’ ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…We adopted the mean ± standard deviation of Pearson's correlation coefficient ( Bear et al., 2018 ; Schaufelberger et al., 2019 ; Serinagaoglu Dogrusoz et al., 2019 ) as a measure of disagreement between our inference predictions and the ‘target data’ ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…That is, the detection of focal activity, and epicardial breakthrough sites can be missing or misplaced. The problem is seen not only with clinical data [5] but also in torso tank experiments [1], [4] and in simulated data [7], [8] where forward models are well defined, suggesting that the issue lies with the inverse methods themselves.New inverse methods are therefore needed to improve the performance and the accuracy of ECGI in the reconstruction of focal activity, and epicardial breakthrough sites.…”
Section: Introductionmentioning
confidence: 99%
“…ECGI has successfully been used to provide electroanatomic mapping of arrhythmogenic substrates [2] and detect responders to cardiac resynchronization therapy [3]. However, recent validation studies have demonstrated that current implementations may detect artificial lines of block that are not seen in contact electrograms [4][5][6]. This raises the question whether ECGI can detect and locate slow conduction zones when they are present.…”
Section: Introductionmentioning
confidence: 99%